The Effectiveness of the JEBOL ANDUK (Jemput Bola Administrasi Kependudukan) Programme - Rahmawati, Ervinda; Hertati, Diana (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Seeing the large number of residents in Surabaya City and the higher percentage of population growth, the Surabaya City Government made an innovation, namely the JEBOL ANDUK (Jemput Bola Administrasi Kependudukan) Programme. The program aims to maximise population administration services to the community and create an orderly population administration. Gebang Putih Village is one of the villages in Sukolilo Sub-district with a high percentage of orderly population administration.   This research was analysed using the theory of program effectiveness by Budiani, there are several aspects to determine the effectiveness of a program, namely 1) Accuracy of program targets; 2) Socialisation of the programme; 3) Programme objectives; and 4) Programme monitoring.  The programme has been implemented effectively, as seen from the success of the programme implementation, which has increased from the previous year. This can be seen from the first success, namely the increased level of community participation in the programme. Second, the decrease in the number of people without legal identity documents before and after the programme. Third, community satisfaction with the accessibility and quality of services provided. Fourth, the programme reached vulnerable and underserved groups. Effectiveness of the administrative ball pick-up programme implementation. The JEBOL ANDUK program is not only successful in its implementation, but also has a significant positive impact on the community, especially in terms of improving access and quality of population administration services. The success of this program makes an important contribution to improving the effectiveness of population administration management at the local level.